2022
DOI: 10.3390/ijerph19063639
|View full text |Cite
|
Sign up to set email alerts
|

Surface Functionalization of Non-Woven Fabrics Using a Novel Silica-Resin Coating Technology: Antiviral Treatment of Non-Woven Fabric Filters in Surgical Masks

Abstract: Masks are effective for preventing the spread of COVID-19 and other respiratory infections. If antimicrobial properties can be applied to the non-woven fabric filters in masks, they can become a more effective countermeasure against human-to-human and environmental infections. We investigated the possibilities of carrying antimicrobial agents on the fiber surfaces of non-woven fabric filters by applying silica-resin coating technology, which can form silica-resin layers on such fabrics at normal temperature an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…While the stability of HCoV on surfaces for up to 6 days is reported in the literature, the characteristics of the surface greatly influence virus persistence . Melt-blown PP is hydrophobic with high filtration efficiency and may accelerate virus inactivation or interfere with virus recovery . In 6 h, 30DAOH and 40DAOH exhibited around 2.5 log reduction in the titer of HCoV corresponding to >99.7% reduction of the viral load.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…While the stability of HCoV on surfaces for up to 6 days is reported in the literature, the characteristics of the surface greatly influence virus persistence . Melt-blown PP is hydrophobic with high filtration efficiency and may accelerate virus inactivation or interfere with virus recovery . In 6 h, 30DAOH and 40DAOH exhibited around 2.5 log reduction in the titer of HCoV corresponding to >99.7% reduction of the viral load.…”
Section: Resultsmentioning
confidence: 93%
“…77 Melt-blown PP is hydrophobic with high filtration efficiency and may accelerate virus inactivation or interfere with virus recovery. 78 In 6 h, 30DAOH and 40DAOH exhibited around 2.5 log reduction in the titer of HCoV corresponding to >99.7% reduction of the viral load. This reduction in the titer value is significantly higher when compared to the control surfaces, which demonstrated only 1.1 log reduction over 6 h. After 24 h, the titer of HCoV reduced to the limit of detection values with both the control and catechol-containing coatings.…”
Section: Antibacterial Activity Of Polymer-coated Pp Fabricsmentioning
confidence: 92%
“…A recent study demonstrated the formation of a protective silica−resin film containing an antimicrobial agent such as hinokitiol on the surface of nonwoven fabric used in medical masks. 26 This protective coating was found to have an excellent antimicrobial effect. We believe that our silica−resin coating technology can be applied to a wide variety of products, from everyday necessities to industrial products, to assist in the transition to a more sustainable and safe society through the use of paper or other materials rather than plastics.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, coated paper would provide waterproof and antimicrobial cutlery that is readily disposed of without causing environmental harm. A recent study demonstrated the formation of a protective silica–resin film containing an antimicrobial agent such as hinokitiol on the surface of nonwoven fabric used in medical masks . This protective coating was found to have an excellent antimicrobial effect.…”
Section: Resultsmentioning
confidence: 99%
“…With the COVID-19 epidemic attacking the world, melt-blown nonwovens (MBs), as the core of masks, serve as the most effective solution to protect ourselves from the spread of droplets carrying the virus and aerogels in the air, becoming an indispensable material. 1,2 At present, the MBs on the market are almost all made of polypropylene (PP) that is non-degradable and difficult to recover, causing a great threat to the environment. 3 As a bio-based biodegradable polymer, polylactic acid (PLA) comes from renewable resources such as straw and starch in crops and is easy to recycle or decompose, having an advantage in disposable protective equipment.…”
Section: Introductionmentioning
confidence: 99%